Application of electrolytic manganese residues in cement products through pozzolanic activity motivation and calcination. (1st March 2022) - Wang, Fan; Long, Guangcheng; Bai, Min; Wang, Jilin; Zhou, John L.; Zhou, Xiang
Abstract: Degradation in grade of manganese ore aggravates the complexity of electrolytic manganese residue (EMR). Calcination is one of the most practical pretreatment methods to improve EMR activity and dispose the hazardous elements. In this paper, the evolution of mineral phase, pozzolanic activity, pore structure and harmful components induced by calcining EMR was investigated. The results show that EMR calcined at 800 °C has the strength activity index (SAI) of 84.79 at 28 d, which is attributed to the decomposition of dihydrate gypsum and the formation of activated calcium, silicon and aluminum oxide. The formation of β-type hemihydrate gypsum increases the pozzolan activity, while the latter is limited by the formation of stable Mn-spinel (Mn3 O4 ) and Mn-hercynite (MnFe2 O4 ). In the EMR-doped mortar matrix, the production of a large amount of ettringite due to the existence of gypsum, as well as common C-S-H, portlandite and AFm, which strongly verify the pozzolanic activity of EMR. Leaching results show that Mn 2+ and NH4 + -N could not be eliminated completely at low temperature (<600 °C), but could be completely stabilized in the alkaline environment provided by the cement. The Mn 2+ and NH4 + -N levels in mortar are fully below the regulatory standards when calcinated above 800 °C. All heavy metals are fixed in the cement and calcination process, ensuring the cleaner utilization of EMR in building materials. Graphical abstract: Image 1 Highlights: EMR calcined at 800 °C has the optimum strength activity index of 84.79 at 28-d. Pozzolan activity of EMR is boosted in β-CaSO4 ·0.5H2 O and weakened in Mn3 O4 and MnFe2 O4 . Presence of gypsum in EMR retards the cement hydration and forms ettringite. Mn 2+ and NH4 + -N below national standards at calcination above 800 °C.